APPLICATION OF GOOGLE CLASSROOM-BASED BLENDED LEARNING MODEL IN CREATIVE PRODUCT AND ENTREPRENEURSHIP LEARNING SUBJECTS IN SMK NEGERI 1 PALANGKA RAYA - Erin Kristina; Pantur Pandiangan; Samuel Layang (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2020)
This study aims to determine student learning outcomes and student responses using the Google classroom-based Blended Learning method. This research is a descriptive study with a quantitative approach. The research sample was 26 students of class XII KGSP SMK N 1 Palangka Raya academic year 2019/2020. The research instrument was a learning outcome test and a questionnaire. The learning outcome test is in the form of multiple-choice consisting of a pre-test and a post-test. The results showed that classical completeness at the pre-test was 3.85%, and after applying the Blended Learning Model (post-test), classical completeness was 100%. Student response to the use of Google Classroom was 76.27% which is categorized as a very strong response.